ANALYSIS OF ECOSYSTEM SERVICES IN THE SEMIARID LANDSCAPE OF THE BASIN OF CREEK SÃO JOSÉ, PERNAMBUCO - Chaves, Ana Maria Severo; Vieira, Alexandre Gomes Teixeira; França, Elaynne Mirele Sabino de; Santos, Evandro José dos; Teixeira, Gisele dos Santos Silva; Silva, Josefa Inayara dos Santos; Melo e Souza, Rosemeri (Geosaberes; Vol 12 (2021)DO - 10.26895/geosaberes.v12i0.1147, 2021)
The semi-arid comprises singular dynamics represented by the adaptive capacity of vegetation and the provision of ecosystem services (ES) that, directly and indirectly, provide well-being to humanity. In this context, the objective was to identify the provision of ecosystem services in the semi-arid landscape of the Riacho São José Basin in Pernambuco according to the different classes of land cover. The methodology is based on the technical guidelines of the Common International Classification of Ecosystem Services, fieldwork, geographic information systems and RAW Graphs platform. Such procedures allowed the identification of 51 SE, of which 22 are provision, 19 with the function of regulation and maintenance and 10 of a cultural nature. Thus, the identification of SE in the basin comprises indicators that should guide the environmental planning and sustainable management of the Lands.